2022
DOI: 10.1021/acs.joc.1c02644
|View full text |Cite
|
Sign up to set email alerts
|

Anodic C(sp3)–H Acyloxylation of Indolin-3-ones Enabled by Oxidant-Free Cross-Dehydrogenative C(sp3)–O Coupling

Abstract: An efficient anodic C­(sp3)–H acyloxylation protocol has been established via intermolecular cross-dehydrogenative C­(sp3)–O coupling. The protocol provides various C2-acyloxy indolin-3-ones without the addition of metal catalysts and external oxidants because indolin-3-ones can be directly oxidized at the anode. The effective application of several medical drugs and the realization of the gram-scale experiment have proven the practicality of this protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…In 2022, the Huang group reported the electrochemical acyloxylation of indolin-3-ones, which can furnish a range of C2-acyloxy indolin-3-ones in acceptable and excellent yields in the absence of metal catalysts and external oxidants through cross-dehydrogenative C(sp 3 )–O coupling (Scheme 27). 34 The authors found that bromide ions could play an important role in this reaction, since no acyloxylated products can be afforded when the reaction was performed without the addition of n -Bu 4 NBr. Noteworthily, some drugs and bioactive molecules can be tolerated, and the practicality of this protocol has been well illustrated.…”
Section: Electrochemical Functionalization Of the Pre-existing Oxindolesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, the Huang group reported the electrochemical acyloxylation of indolin-3-ones, which can furnish a range of C2-acyloxy indolin-3-ones in acceptable and excellent yields in the absence of metal catalysts and external oxidants through cross-dehydrogenative C(sp 3 )–O coupling (Scheme 27). 34 The authors found that bromide ions could play an important role in this reaction, since no acyloxylated products can be afforded when the reaction was performed without the addition of n -Bu 4 NBr. Noteworthily, some drugs and bioactive molecules can be tolerated, and the practicality of this protocol has been well illustrated.…”
Section: Electrochemical Functionalization Of the Pre-existing Oxindolesmentioning
confidence: 99%
“…The key radical species 70 , formed by the deprotonation and oxidation of 67 , could be converted to the N -acyliminium ion 71 under electrochemical conditions, which could form a new C–O bond through the interaction of 72 (Scheme 28). 34…”
Section: Electrochemical Functionalization Of the Pre-existing Oxindolesmentioning
confidence: 99%
“…As a subclass of these, α-amino sulfides with important biological activity and medicinal value have long encouraged organic chemists to explore novel methods dedicated to their synthesis. To the best of our knowledge, there have been relatively few previous reports on the synthesis of α-amino sulfides, the key to which is the formation of C–S bonds …”
mentioning
confidence: 99%
“…1). 1,2 Due to their fascinating structures and promising biological activities, much attention has been paid to the construction of various 2,2-disubstituted indolin-3-ones, among which oxidative rearrangement of 2,3-disubstituted indoles, 3 direct conversion reaction of 3 H -indol-3-ones or indolin-3-ones, 4 and oxidative dearomatization 5 represent the main synthetic routes from cyclic starting materials.…”
mentioning
confidence: 99%